1983
DOI: 10.1577/1548-8659(1983)112<800:ioasoo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ambient Salinity on Osmoregulation and Cortisol Concentration in Yearling Coho Salmon during Stress

Abstract: Yearling coho salmon Oncorhynchus kisutch acclimated to fresh water or seawater were subjected to severe chronic confinement stress in fresh water, seawater, or a medium (one‐third‐strength seawater) that was approximately isosmotic to the fishˈs blood. Plasma osmolarity, Na, K, Ca, Mg, and cortisol and blood hematocrit were measured in fish sampled at 1, 7, 24, and 48 hours after stress began. Plasma osmolarity and electrolyte concentrations increased during stress in seawater, but generally decreased during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
60
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 0 publications
11
60
2
Order By: Relevance
“…Additionally, the significant difference was also observed in Na + and Cl -ion concentrations after pumping suggests a net transepithelial fluxe of Na + and C1 -change in these euryhaline fish during stress (Redding and Schreck 1983).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Additionally, the significant difference was also observed in Na + and Cl -ion concentrations after pumping suggests a net transepithelial fluxe of Na + and C1 -change in these euryhaline fish during stress (Redding and Schreck 1983).…”
Section: Discussionmentioning
confidence: 79%
“…Earlier studies have also demonstrated that blood osmolality and electrolyte concentrations are similarly affected when fish are handled and transported (Redding andSchreck 1983, Urbinati et al 2004). Osmotic perturbations during stress are affected directly by changes in branchial permeability to water and electrolytes (Redding and Schreck 1983) and the magnitude and direction of stress-induced osmotic imbalance depends, at least partly, on water salinity. Fish stressed in seawater tend to gain electrolytes and lose water (Redding andSchreck 1983, Urbinati et al 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This seemed to be supported by the fact that secondary and tertiary stress responses as plasma chloride, magnesium, fin rot and mortality, were significantly increased in the "stress and vaccine" group compared to the "vaccine and stress" and the control group. Earlier studies have shown that cortisol is often associated with the detrimental effects of stress including: decreased growth rates, reproductive dysfunction (Morgan et al 1999;Schreck et al 2001;Mommsen et al 1999), increased incidence of disease (Barton 2002;Davis et al 2002Davis et al , 2003Einarsdottir et al 2000a;Einarsdottir et al 2000b;Weyts et al 1999), reduced seawater tolerance (Ventura et al 2011;Iversen et al 2009;Mommsen et al 1999;Redding and Schreck 1983;Sandodden et al 2001) and survival (Iversen et al 2005;Portz et al 2006;Finstad et al 2003;Iversen et al 1998;Hasan and Bart 2007). It has also been suggested that if the fish is not permitted enough time to recover completely after stress, a second, normally nonfatal, stressful occurrence could be fatal (Carmichael 1984), as observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, of course, that this hormone is playing some other, nonhydromineral (Clarke and Bern, 1980) or immunologic role after stress in either medium. Similarly, the hyperkaliemia following stress in either FW-or SWadapted fish could reflect compensation for stress-induced acid-base imbalance (Redding and Schreck, 1983;Turner et al, 1983).…”
Section: Discussionmentioning
confidence: 99%